Streptobacillus notomytis sp. nov., isolated from a spinifex hopping mouse (Notomys alexis Thomas, 1922), and emended description of Streptobacillus Levaditi et al. 1925, Eisenberg et al. 2015 emend - Eisenberg, Tobias; Glaeser, Stefanie P.; Ewers, Christa; Semmler, Torsten; Nicklas, Werner; Rau, Jörg; Mauder, Norman; Hofmann, Nicola; Imaoka, Koichi; Kimura, Masanobu; Kämpfer, Peter (International journal of systematic and evolutionary microbiology, 2015)
A pleomorphic, Gram-negative, rod-shaped, indole-, oxidase- and catalase-negative, non-spore-forming, non-motile bacterium was isolated in 1979 from the heart of a spinifex hopping mouse ( Notomys alexis Thomas, 1922) with septicaemia and stored as Streptobacillus moniliformis in the strain collection of the Animal Health Laboratory, South Perth, Western Australia (AHL 370-1), as well as under CCUG 12425. On the basis of 16S rRNA gene sequence analyses, the strain was assigned to the genus Streptobacillus , with 99.4 % sequence similarity to the type strain of Streptobacillus moniliformis , 95.6 % sequence similarity to the type strain of Streptobacillus hongkongensis and 99.0 % sequence similarity to the type strain of Streptobacillus felis . The clear differentiation of strain AHL 370-1 T from Streptobacillus moniliformis , Streptobacillus hongkongensis and Streptobacillus felis was also supported by rpoB , groEL and recA nucleotide and amino acid sequence analysis. Average nucleotide identity was 87.16 % between strain AHL 370-1 T and Streptobacillus moniliformis DSM 12112 T . Physiological data confirmed the allocation of strain AHL 370-1 T to the family Leptotrichiaceae , considering the very similar profiles of enzyme activities and fatty acids compared to closely related species. Within the genus Streptobacillus , isolate AHL 370-1 T could also be separated unambiguously from the type strains of Streptobacillus moniliformis, Streptobacillus hongkongensis and Streptobacillus felis by MALDI-TOF mass spectrometry. Two further strains (KWG2 and KWG24) isolated from asymptomatic black rats in Japan were highly similar to AHL 370-1 T . On the basis of these data, we propose the novel species Streptobacillus notomytis sp. nov., with the type strain AHL 370-1 T ( = CCUG 12425 T = DSM 100026 T = CCM 8593 T = EF 12425 T ).